Estudo do comportamento mecânico de solo da formação Guabirotuba com adição de cal e pó de vidro - Pudell, Paula Caroline Alves (2022)
The main purpose of this research study was to evaluate the mechanical behavior of a soil from the Guabirotuba formation, improved with lime and glass powder (PV). The contents used for lime were 3%, 7% and 10% and for PV were 2% and 5%, these contents were combined, thus developing 6 samples (M1-M6). To characterize the primary materials (soil, lime and PV) the granulometric analysis, real grain density (Gs) and X-ray fluorescence (FRX) tests were performed. For the 6 samples and the soil were applied the Atterberg Limits tests, compaction at normal, intermediate and modified energies, tests of simple compressive strength (qu) and tensile strength by diametric compression (qt) for four curing times (0, 7, 28 and 60 days) and in the three compaction energies. Resistance tests were performed in four replicates, determined by the minimum sample method, to allow statistical treatment. And all the samples were analyzed by scanning electron microscope (SEM) and by X-ray diffraction (DRX). From the tests, the soil was classified as high plasticity silt (MH). Through the consistency limit tests, it was possible to notice that there were changes in the soil properties with addition of lime and PV, mainly in the M5 and M6 samples, which with the addition of those materials came to be classified as low plasticity silt (ML), for M6 a 57% reduction in IP compared to pure soil was also observed. In relation to the microstructural analysis of the samples, it was possible to observe the formation of C-S-H and C-A-H on the surface of the mixture M5 and M6. By the compaction tests, the samples have similar behavior in all the applied energies, with a reduction of the maximum dry unit weight (γd,max) and an increase of the optimal humidity (Wot) in relation to the natural soil. In respect of the mechanical strength tests, after statistical comparisons of variance and multiple comparisons of means were made, it is possible to state that the M6 mixture obtained greater increases in strength at 60 days of curing, with an increase of 400% for qu and 875% for qt at normal molding energy. Considerable growth in strength was observed between 0 and 7 days for M5 and M6 at all compaction energies. By way of the resistance tests, the qt/qu ratio was determined including all results and separated by curing time, the total ratio resulted in 0,16. And regarding the curing times, the ratio was 0,14 for 0 days, 0,18 for 7 days, 0,15 for 28 days and 0,16 for 60 days. Based on the results of this research, it is possible to affirm that the use of lime and PV can considerably increase the mechanical strength of the soil, in addition to providing a faster evolution of the strength due to the soillime-pozzolan system.